2022
DOI: 10.1097/adm.0000000000000991
|View full text |Cite
|
Sign up to set email alerts
|

HIV Exposure Prophylaxis Delivery in a Low-barrier Substance Use Disorder Bridge Clinic during a Local HIV Outbreak at the Onset of the COVID-19 Pandemic

Abstract: Objectives: People who inject drugs (PWID) may experience high human immunodeficiency virus (HIV) risk and inadequate access to biomedical HIV prevention. Emerging data support integrating HIV post-exposure and pre-exposure prophylaxis (PEP, PrEP) into services already accessed by PWID. We describe PEP/PrEP eligibility and receipt in a low-barrier substance use disorder bridge clinic located in an area experiencing an HIV outbreak among PWID at the onset of the COVID-19 pandemic. Methods: Retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…For example, a PrEP program at a community health center for people experiencing homelessness that provided directly observed therapy and flexible navigation tailored to the client's need achieved a PrEP retention rate of 44% after 6 months ( Biello et al., 2021 ). In the bridge clinic setting, our finding that 43% of PrEP-eligible patients were on PrEP compares favorably to prior clinic work showing 66% of eligible patients were offered and 14% prescribed PrEP, suggesting important synergy between PRC and the low-barrier clinical settings model ( Braun et al., 2022 ). The impact of the PRC intervention may be less robust in settings without resources designed to meet the clinical needs of PWID.…”
Section: Discussionsupporting
confidence: 51%
“…For example, a PrEP program at a community health center for people experiencing homelessness that provided directly observed therapy and flexible navigation tailored to the client's need achieved a PrEP retention rate of 44% after 6 months ( Biello et al., 2021 ). In the bridge clinic setting, our finding that 43% of PrEP-eligible patients were on PrEP compares favorably to prior clinic work showing 66% of eligible patients were offered and 14% prescribed PrEP, suggesting important synergy between PRC and the low-barrier clinical settings model ( Braun et al., 2022 ). The impact of the PRC intervention may be less robust in settings without resources designed to meet the clinical needs of PWID.…”
Section: Discussionsupporting
confidence: 51%
“…In addition to MOUD, bridge clinics generally offer pharmacotherapy for other types of SUD, such as naltrexone and acamprosate for alcohol use disorder, and some bridge clinics incorporate HIV, viral hepatitis, and bacterial sexually transmitted infection (STI) screening, treatment, and prevention services like HIV pre-and post-exposure prophylaxis (PrEP, PEP) to address unmet need [23,33]. On-site access to vaccines and commonly used antibiotics for STI treatment facilitates ready delivery of these services at the point of care.…”
Section: Hospital-based Outpatient Bridge Clinicsmentioning
confidence: 99%
“…In addition, bridge clinics also offer low-barrier STI, viral hepatitis, and HIV screening, treatment, and prevention, including point-of-care rapid HIV testing, PrEP, and PEP [33]. Some clinics also offer an array of wrap-around clinical services ranging from emergency contraception, long-acting reversible and injectable contraception, wound care, and interim primary care to support engagement and address unmet needs.…”
Section: Harm Reduction Service Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bridge clinics have emerged as a model for transitional care that engages people who use drugs at risk of HIV, including WSWUD [ 22 ]. Some bridge clinics have the clinical infrastructures supportive of PrEP initiation, namely access to phlebotomy and providers with prescribing privileges [ 23 ]. Studies from a single Boston-based bridge clinic demonstrated successful PrEP initiation within this clinical setting [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%